LAND USE CHANGE AND RECOMMENDATION FOR SUSTAINABLE DEVELOPMENT OF PEATLAND FOR AGRICULTURE: Case Study at Kubu Raya and Pontianak Districts, West Kalimantan - Wahyunto, Wahyunto; Supriatna, Wahyu; Agus, Fahmuddin (Indonesian Agency for Agricultural Research and Development - MOA, 2010)
Peatland is an increasingly important land resource for livelihood,economic development, and terrestrial carbon storage. Kubu Raya and Pontianak Districts of West Kalimantan rely their future agricultural development on this environmentally fragile peatland because of the dominance (58% and 16% area, respectively) of this land in the two districts. A study aimed to evaluate land use changes on peatland and to develop strategies for sustainable peatland use and management for agriculture. Time series satellite imageries of land use and land cover,ground truthing, and statistical data of land use change were analyzed for generating the dynamics of land use changes in the period of 1986-2008. Field observation, peat sampling, and peat analyses of representative land use types were undertaken to assess peat characteristics and its agricultural suitability. The study showed that within 22 years (1986-2008), the area of peat forests in Kubu Raya and Pontianak Districts decreased as much as 13.6% from 391,902 ha to 328,078 ha. The current uses of the peatland in the two districts include oil palm plantation (8704 ha), smallholder rubber plantation (13,186 ha), annual crops (15,035 ha), mixed cropping of trees and annual crops (22,328 ha), and pineapple farming (11,744 ha). Our evaluationshowed unconformity of the current uses of peatland with regulations and crops agronomic requirements such as peat thickness and maturity, rendering unsustainability. This study recommends that expansion of agriculture and plantation on peatland areas be limited over idle land within the agricultural production and conversion production forest areas. About 34,362 ha (9.7%) of uncultivated log-over forest and shrubscan potentially be developed for agriculture. Peat soils with the thickness of >3 m should be allocated for conservation or forest protection due to low inherent soil fertility and high potential greenhouse gas emissions if converted for agriculture.